Tingkat Kepuasan Pasien terhadap Pelayanan Kefarmasian di Apotek Medika Usada - Luh Adi Kusuma Suardiani; Kristina, Ni Kadek Putri Nanda (IAI Nasional Laa Roiba Bogor, 2024)
Patient satisfaction measures patients’ emotional responses towards pharmacists’ services. It is based on tangible aspects like the pharmacy’s appearance, reliability, responsiveness, assurance, and empathy. It is influenced by the fulfilment of patient expectations, the availability and completeness of medications, and the staff’s friendliness. This research uses descriptive research from 20 May to 4 June 2024. The satisfaction of prescription services is measured using a validated questionnaire. The sample used consists of 96 respondents who meet the inclusion criteria. The data obtained from the questionnaire results were then calculated to determine the percentage of patient satisfaction, which can subsequently be categorized as satisfied or dissatisfied based on the established percentages. The result indicates that patient satisfaction based on reliability is 74.21%, categorized as satisfied. Responsiveness is 74.58%, and it is categorized as satisfied. Assurance is 73.85%, categorized as satisfied. Empathy is 75.15%, categorized as satisfied, and Tangibles is 74.11%, categorized as satisfied. From the five dimensions, an average score of 74.38% was obtained, categorized as satisfied according to the percentage range of 61-80%, which indicates a satisfied rating. Based on the data analysis and discussion above regarding the patient satisfaction questionnaire related to pharmaceutical services at Medika Usada Pharmacy, it can be concluded that patients feel satisfied with the services provided.